The Photoromance: A Feminist Reading of Popular Culture, Paola Bonifazio (2020)1. Issue 1 (1st January 2022) - Buonanno, Milly
Review of: The Photoromance: A Feminist Reading of Popular Culture, Paola Bonifazio (2020)Cambridge: MIT Press, 248 pp., ISBN 978-0-26253-923-9, p/bk, 29.95